Macrophage activation syndrome in adult systemic lupus erythematosus: report of seven adult cases from a single Italian rheumatology center - F. Dall'Ara (Reumatismo, 2018)
The aim was to describe the macrophage activation syndrome (MAS), a life-threatening syndrome characterized by excessive immune activation that can be triggered by conditions affecting immune homeostasis, in a cohort of adult Italian patients with systemic lupus erythematosus (SLE). This was a monocentric retrospective evaluation. The utility of the H-score, developed to estimate the individual risk of having reactive MAS in adult patients, was assessed. Among 511 patients with SLE, 7 cases (1.4%) of MAS (all females) were identified and their medical records reviewed. In all cases, MAS was simultaneous to the onset of SLE. All patients had fever, lymphadenopathy, hematological involvement, and high titer of anti-dsDNA antibodies. Workup for infections and malignancies was negative. In all cases, the H-score was higher than the cut-off suggested for the classification of reactive MAS. All cases required hospital admission, and 2 patients were admitted to the intensive care unit. Most patients were treated successfully with high doses of corticosteroids and with immunosuppressive drugs, whereas the full therapeutic regimen developed for primary hemophagocytic lymphohistiocytosis HLH was used only in one case. No death from MAS was observed. MAS is a rare and severe disorder that complicated the onset of SLE in our cohort. The H-score may be useful in the classification of these patients.